The effect of acetate Ringer's solution versus lactate Ringer's solution on acid base physiology in infants with biliary atresia - Xiang Liu; Hongyan Cao; Xiaona Tan; Jing Shi; Li Qiao; Qi Zhang; Lei Shi (BMC, 2021)
Abstract Background The choice of the perioperative crystalloid is a key component of the fluid management and must take into account the liver function and the appearing metabolic disorders to avoid increase the liver extra metabolism. The aim of this study is to analyze the effect of acetate Ringer's solution or lactate Ringer's solution in biliary atresia patients. Methods We included 68 infant patients aged between 21 ~ 65 d, ASA physical status II or III, who underwent elective Kasai hepatoportoenterostomy, received either AR and LR for intravenous fluid resuscitation according to their group allocation. Lactate concentration, serum electrolytes and pH were noteded before skin incision (T1), end of surgery (T2) and postoperative 12 h. We also recorded the time of operation, stay of hospital, loss of blood and urinary, total volume of infusion of crystalloid. Results Lactate level was significantly higher in Group LR than in Group AR patients at T2 (0.76 ± 0.13 versus 0.57 ± 0.22, P = 0.03). Compared with T3, sodium and chlorine were significantly higher in two groups at T2 (145.2 ± 3.1 versus 143.4 ± 3.4 and 104.6 ± 3.7 versus 105.2 ± 2.1). No significant differences were noted in potassium, HCO3 − and calcium. There was no statistically significant difference in pH. No glycopenia was recorded in two groups. No significant difference was noted in administration of vasoactive drug (0.7% versus 1%). Conclusions Resuscitation with AR and LR was associated with similar clinical improvement in infants with biliary atresia. Use of AR reduced the level of lactate comparison with LR.